Geothermal Electricity: Potential For Co2 Mitigation - Schütz, Felina; Huenges, Ernst; Spalek, Angela; Bruhn, David; Pérez, Paloma; de Gregorio, Margarita (Zenodo, 2013)
The provision of energy addresses societal and political issues for the present and future generations. A goal, which is defined in the Kyoto and post-Kyoto targets, is to increase the share of renewable energies in the future energy concepts, in order to mitigate greenhouse gas emissions and reduce the consumption of finite energy resources. The development of geothermal energy for electricity production and particularly the use of Enhanced Geothermal Systems (EGS) are promising options in this context. EGS are supposed to make a large contribution to a sustainable energy mix, in the future. This means that, besides improving technical aspects, the use of geothermal energy must be realizable with a climate friendly lifecycle and competitive energy production costs. In the present study the potential of geothermal electricity regarding CO2 mitigation will be discussed, considering CO2-emissions of different energy sources and particularly of the different geothermal power plants on-line today. Technical potential deployment is estimated based on different literature sources and the resource assessment study developed within the framework of the GEOELEC Project. CO2-mitigation calculations of different studies will be discussed considering the technical potential. : GEOELEC - IEE : {"references": ["\u00c1rmannsson, H., Thr\u00e1inn, F., Kristj\u00e1nsson, B. R. (2005). CO2 emissions from geothermal power plants and natural geothermal activity in Iceland, Geothermics, 34, 286\uf02d296.", "Beardsmore, G., Rybach, L., Blackwell, D., Baron, C. (2010). A Protocol for estimating and mapping the global EGS potential. Proc. Australian Geothermal Conference 2010, pp. 257-262", "Bertani, R., Thain, I. (2002). Geothermal power generating plant CO2 emission survey. IGA News 49, 1\u20133.", "Bloomfield, K. K., Moore, J. N., Neilson, R. N. (2003). Geothermal energy reducesgreenhouse gases. Geothermal Resources Council Bulletin, 32, 77\u201379.", "IEA, (2012). CO2 Emissions from Fuel Combustion \u2013 Highlights. International Energy Agency, IEA (Edition 2012).", "Frick, S, van Wees, J.D., Kaltschmitt, M., Schr\u00f6der, G. (2010). Economic performance and environmental assessment, in Enhanced Geothermal Energy Systems,Geothermal Technology for Resource Assessment,Exploration, Field Development, andUtilization (ed. E. Huenges), John Wiley &Sons, Ltd, in press.", "Fridleifsson, I.B., Bertani, R., Huenges, E., Lund, J. W., Ragnarsson, A., Rybach, L. (2008). The possible role and contribution of geothermal energy to the mitigation of climate change, in IPCC Scoping Meeting on Renewable Energy Sources, Proceedings (eds O. Hohmeyer and T. Trittin), L\u00fcbeck, January 20\u201325, 2008, pp. 59\u201380.", "Goldstein, B., Hiriart, G., Bertani, R., Bromley, C., Gutierrez-Negrin, L., Huenges, E., Muraoka, H., Ragnarsson, A., Tester, J., Zui, V. (2011). Geothermal Energy. In IPCC Special Report on Renewable Energy Sources and Climate Change Mitigation [O. Edenhofer, R. Pichs-Madruga, Y. Sokona, K. Seyboth, P. Matschoss, S. Kadner, T. Zwickel, P. Eickemeier, G. Hansen, S. Schlomer, C. von Stechow (eds)], Cambridge University Press, Cambridge, United Kingdom and New York, NY, USA.", "Holm, A., Jennejohn, D., Blodgett, L., GEA (2012). Geothermal Energy and Greenhouse Gas Emissions, Geothermal Energy Association, Report November 2012, http://geoenergy. org/reports/GeothermalGreenhouseEmissionsNov2012GEA_web.pdf.", "Moomaw, W., P. Burgherr, G. Heath, M. Lenzen, J. Nyboer, Verbruggen, A. (2011). Annex II: Methodology. In IPCC Special Report on Renewable Energy Sources and Climate Change Mitigation [O. Edenhofer, R. Pichs-Madruga, Y. Sokona, K. Seyboth, P. Matschoss, S. Kadner, T. Zwickel, P. Eickemeier, G. Hansen, S. Schlomer, C. von Stechow (eds)], Cambridge University Press, Cambridge, United Kingdom and New York, NY, USA.", "Nolasco, L. A. F. (2010). Hydrogen sulphide abatement during discharge of geothermal steam from well pads: a case study of well PAD TR-18, El Salvador. Reports 2010, 13, Geothermal Training Programme, Iceland.", "Sathaye, J., O. Lucon, A. Rahman, J. Christensen, F. Denton, J. Fujino, G. Heath, S. Kadner, M. Mirza, H. Rudnick, A. Schlaepfer, A. Shmakin, (2011). Renewable Energy in the Context of Sustainable 17 Development. In IPCC Special Report on Renewable Energy Sources and Climate Change Mitigation [O. Edenhofer, R. Pichs-Madruga, Y. Sokona, K. Seyboth, P. Matschoss, S. Kadner, T. Zwickel, P. Eickemeier, G. Hansen, S. Schlomer, C. von Stechow (eds)], Cambridge University Press, Cambridge, United Kingdom and New York, NY, USA.", "Stefansson, V. (2005). World geothermal assessment. In: Proceedings World Geothermal Congress 2005, Antalya, Turkey, 24-29 April 2005 (ISBN: 9759833204). Available at: www.geothermalenergy. org/pdf/IGAstandard/WGC/2005/0001.pdf."]}